Dollar store policy opportunities in Baltimore City: community member and policy maker perspectives - Sundermeir, Samantha M.; Santos, Sydney R.; Lewis, Emma C.; John, Sara; Gardner, Karen; Friedman, Emily; Poirier, Lisa; Hua, Shuxian; Peoples-Brown, Sevetra; Benjamin-Neelon, Sara E.; Gittelsohn, Joel (Frontiers in Nutrition, 2024)
The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. The funders had no role in study design, analysis, or decision to publish. Three policy expert staff members from CSPI are included as coauthors on this paper; they assisted with developing the policy discussion component of the workshop scripts, and two (SJ and KG) attended the workshops to assist with policy discussions. All three critically reviewed the final version of the manuscript.